Finite Element Analysis for Torsion Behavior of Flat Web Profile Beam Steel Section with Opening. (2015) - De'nan, Fatimah; Hasan, Hazwani; Nassir, Duaa Khaled; Osman, Mohd Hanim; Saad, Sariffuddin
Abstract: The construction of modern commercial buildings should always incorporate building services while reducing the cost of steel. A frequently used solution is to provide openings at the web of the beams and girders to enable services to pass through. The main objective of this paper is to determine the angle of torsion of a flat-web (FW) profile steel section with openings of different shapes and sizes using LUSAS software. A model consisting of a FW profile beam steel section of five shapes and three sizes of openings has been developed. The shapes of opening are circle, square, regular octagon, C-hexagon, and regular hexagon. The sizes of the opening are 0.5 D, 0.6 D and 0.8 D; D is the height of the web. Based on the results of the analytical investigations, the best shape of the opening is C-hexagon, and best size is 0. 5 D in resistance torsion compared with a FW profile section without opening. When the length of the beam section becomes longer, the value of the rotation angle increases. In general, the value of the angle of rotation for all shapes and sizes is close to the value of the angle of rotation for a FW profile without opening. Hence a flat-web section with opening is suitable in many cases to reduce cost and weight of steel.